The Dynamics of Checks and Balances in the New Administration: Safeguarding the Integrity of the Judiciary in Achieving Substantive Justice - Dwi Kartini; Depi Angga Alpiana; Yovan Iristian (Lex Journal: Kajian Hukum & Keadilan, 2026)
This research examines the critical tension between executive expansion and judicial independence within the context of the 2024 general elections and the emergence of new administrations globally and in Indonesia. Utilizing a normative-legal and comparative approach, the study analyzes the phenomenon of "autocratic legalism," where legal instruments are strategically repurposed to consolidate political power, thereby threatening the traditional framework of checks and balances. The findings indicate a significant global regression in democratic standards, with a 67% "fatality rate" for autocratizing democracies and a measurable decline in judicial constraints on executive power in 61% of nations. In Indonesia, the 2024 transition highlighted structural vulnerabilities in the Constitutional Court, particularly regarding ethical dilemmas and the "judicial capture" of candidate eligibility requirements. The article further explores the paradigm shift from proceduralism to substantive justice, arguing that the realization of equitable outcomes requires judges to adopt a "Justice as Fairness" approach, rooted in natural law and human rights, to balance the inherent power asymmetry between the state and its citizens. The study concludes that safeguarding judicial integrity requires institutional reforms including transparent appointment mechanisms, budgetary autonomy, and a progressive interpretive framework that transcends formalistic legal positivism.